The Chinese version of the revised Diabetes Distress Scale for adults with type 2 diabetes: Translation and validation study - Yu-Yun Zhang; Wei Li; Yu Sheng (Elsevier, 2022)
Objectives: This study aimed to translate the revised 17-item Diabetes Distress Scale (DDS17, 2017) into mandarin (simplified) Chinese and validate the Chinese version of DDS17 (C-DDS17, 2021) among adult patients with type 2 diabetes in China. Methods: A scale translation and cross-sectional validation study was conducted. The DDS17 was translated into mandarin (simplified) Chinese through a five-step process: authorization, forward translation, synthesis, back translation, and amendment. During this session, 59 patients assessed the understandability and readability of the translated scale. From June 7 to September 4, 2021, a cross-sectional study that adhered to the COSMIN checklist was conducted with 400 individuals with type 2 diabetes from three Class A tertiary comprehensive hospitals in Beijing, China. The content, construct, convergent, discriminant validity, and reliability (Cronbach's α coefficient and item-total correlation coefficients) of the C-DDS17 were evaluated. This study was a part of a project registered in the Chinese Clinical Trial Registry (no. ChiCTR2100047071). Results: Among the participants, 33.3% (133/400) of them experienced moderate to high diabetes distress. The content validity indices of the C-DDS17 equaled 1.00. The scale yielded a four-factor structure. The average variances extracted were 0.42-0.57, which was lower than squared correlations. Cronbach's α coefficient was 0.88 for the overall scale and ranged from 0.76 to 0.81 for sub-scales. Corrected item-total correlation coefficients ranged from 0.42 to 0.61. The eighth item ("Feeling that I am often failing with my diabetes routine") was better fit to physician distress than regimen distress but had little influence on the validation results. Conclusions: The C-DDS17 is a reliable and valid instrument for assessing diabetes distress in patients with type 2 diabetes. It is a promising instrument for early identification and management of diabetes distress in clinical practice and trials.